Islamic Education Ideology of Pesantren: A ‎Case Study in Hidayatullah Pesantren ‎Balikpapan - Abdurrohim; Adiyono; Jibril Olaniyi Ayuba (State Islamic Institute of Madura, 2023)
The pesantren system places a strong emphasis on the preservation of traditional Islamic knowledge and practices. The research examines the concept of Islamic education ideology and its implementation process at Hidayatullah Islamic Boarding School. Two research questions were raised to guide this study. A qualitative research design is employed in the study, utilizing descriptive data from written language and respondent-observed behaviors. Additionally, 35 students (a mix of current students and Madrasah Aliyah students) were interviewed by the researchers. Data were collected through documentation, interviews, and observation. The findings demonstrate that, as a component of the Islamic movement in Indonesia, PP Hidayatullah Balikpapan established a formulation of Islamic thought that served as the foundation for the organization's philosophy. K.H. Abdullah Said, the founder of PP Hidayatullah, had this genuine notion, which his successors carried on with. This gave rise to fundamental principles that are connected to the pre-prophetic historical periods in Islamic educational ideology, including self-reliance, leadership, entrepreneurship, responsibility, and problem-solving. The steps of normalization, orientation, internalization, externalization, and objectification that comprise the developing ideological consciousness are influenced by the early suras of the Quran. The internalization of Santri's ideological knowledge is accomplished through both classical and non-classical methods, in addition to the use of pesantren support facilities including mosques, dorms, and madrasahs/schools. In conclusion, PP Hidayatullah Balikpapan creates the foundational principles of the Islamic framework and influences Santri's personal development by formulating the cognitive structure of Islamic education and implementing it inside the classroom.